Pertussis Infection in a Baccalaureate Nursing Program: Clinical Implications, Emerging Issues, and Recommendations - Matthews, Ellyn (2008)
Pertussis is a significant public health problem with a dramatic rise in reported cases. Academic and clinical nursing educators are challenged to develop policies based on evolving national immunization guidelines. Of relevance to clinical educators, several outbreaks involving health care facilities and universities have been reported in the past few decades because of failure to adequately recognize pertussis infection and treat disease spread among adults and lack of control measures. The purpose of this article is to present information about pertussis transmission in a baccalaureate nursing program, outline actions taken, and explore emerging issues and recommendations.